PENGARUH PARTISIPASI MASYARAKAT TERHADAP HASIL PEMBANGUNAN DI KAMPUNG LONG ALANGO KECAMATAN BAHAU HULU KABUPATEN MALINAU - Ajang, Ngang (PREDIKSI, 2012)
ABSTRACTThe purpose of this study was to determine whether participation affects the outcome of development in the village. To obtain the necessary data the authors conducted research in the village of Long Alango District Bahau Malinau Hulu.The results showed that:1) There is a positive correlation between the variables of community participation to the implementation of development. This is evident from the results of the calculation of the correlation of two variables where rs empirical correlations obtained greater theoretical rs when compared with the level of trust 95% for N = 30; 0,758 ≥ 0,306.2) The research hypothesis that has the writer suggested to be accepted as true. This is evident where the calculation of the formula test of hypothesis testing with t, t obtained empirical greater than the theoretical t at 95% confidence level for N - 2 (30-2) = 28 are: 6.145 ≥ 1.701. If participation increases, the implementation of development are likely to increase as well and quot.